The importance of using ontologies as a tool for organizing and representing knowledge in police investigation - Uchôa , Alexandre Pereira de Macêdo; Sales, Rodrigo de (Advanced Notes in Information Science, 2023)
This text stems from a theoretical intersection between Information Science and Police Science, specifically in the field of Police Investigation, where it is proposed to demonstrate the importance of using ontologies as a method of organizing and representing knowledge and providing different benefits to the investigation cycle and consequently to its final product. For this purpose, theoretical and introductory aspects were listed on the representation and organization of knowledge in Information Science through ontologies, as well as the description and main informational flows of the Police Investigation cycle assigned to the Judiciary Police. In the end, we sought to demonstrate the benefits of such a technique under Semantic Interoperability, which has the potential to provide greater efficiency and effectiveness to Police Investigation with the improvement of information management and management of the knowledge inherent to the investigative cycle.